Aggregation And Sedimentation Of Electrosterically Stabilized Iron Oxide Nanoparticle - Hamzah, Tengku Nur Amalina Tengku Ahmad Suharizam (Universiti Sains Malaysia, 2017)
The bare magnetic iron oxide nanoparticles (MIOPs) and Poly(sodium(4)styrenesulfonate) PSS-coated-MIOPs are prepared in order to study the colloidal stability and the sedimentation kinetic of the nanoparticles. The PSS-coated-MIOPs are more stable than the bare MIOPs due to electrosteric repulsion between particles that resist the aggregation and sedimentation. The zeta potential of MIOPs after coated with PSS is -34.03 mV. The value of zeta potential larger than 30 mV indicates that the samples have good colloidal stability. The bare MIOPs and PSS-coated-MIOPs are diluted into five different concentrations (10 ppm - 500 ppm). The bare MIOPs are aggregated and sediment faster than PSS-coated-MIOPs. The aggregation and sedimentation is enhanced when the external magnetic source exerted on bare MIOPs and PSS-coated-MIOPs because it experienced magnetophoresis force. The highest concentration of bare MIOPs which is 500 ppm settle first because more concentrated MIOPs have higher collision frequency thus it aggregated and sediment faster. The gravitational force is depends on the size of particles and the large aggregates more responsive towards the magnet. The PSS-coated-MIOPs only has little sediment at the bottom of the sample. The hydrodynamic sizes of samples are measured using dynamic light scattering (DLS). From DLS measurement, PSS-coated-MIOPs have smaller hydrodynamic size than bare MIOPs for all range of concentrations. The hydrodynamic size of PSS-coated-MIOPs is almost constant whereas the hydrodynamic size of bare MIOPs is fluctuated throughout the measurement time for all range of concentration due to formation of large aggregates and small aggregates.